A human rights violation study: The relationship between gender and ambivalent sexism in faculty of health sciences students. Issue 7 (7th July 2021) - Fiskin, Gamze; Sari, Esra
Abstract: The objective of this study was to contribute to the literature by identifying gendered attitudes and ambivalent sexism of students who are health professionals of the future. The sampling of this study, which is planned as a descriptive and correlational study, consists of students studying at departments of midwifery and nursing in two universities in Turkey. Students completed questionnaires that included demographic information, Gender Roles Attitude Scale, and Ambivalent Sexism Inventory. Results showed that students have traditional attitudes toward gender roles, and particularly male students have more negative and conservative gendered attitudes. Also, there was a sexist attitude difference between the two groups. There was a weak positive relationship between gender roles and ambivalent sexism in the study. These findings can raise awareness about sexism for students studying in the health sciences and enable them to provide equal healthcare to all.